Long-Term Safety of PEGylated Coagulation Factor VIII in the Immune-Deficient Rowett Nude Rat. (28th March 2017) - Rasmussen, Caroline E.; Nowak, Jette; Larsen, Julie M.; Moore, Emma; Bell, David; Liu, Kai Chiu; Sorensen, Nanna Skall; Kappers, Wendela A.; Krogh-Meibom, Thomas; Offenberg, Hanne
Abstract : Turoctocog alfa pegol (N8-GP) is a glycoPEGylated human recombinant factor VIII for the treatment of hemophilia A. The safety profile of rFVIII, and polyethylene glycols (PEG) technology, is well-established. Conducting long-term toxicity studies in animals using human proteins can be complicated by anti-drug antibody (ADA) development. To evaluate long-term safety of N8-GP, 26- and 52-week toxicity studies were conducted in immune-deficient rats dosed intravenously every fourth day with 0, 50, 150, 500, or 1200 IU/kg N8-GP. Observations included clinical observations, body weight, ophthalmoscopy, hematology, chemistry, coagulation, urinalysis, toxicokinetics, antibody analysis, and macroscopic/microscopic organ examination. Immunohistochemical staining examined the distribution of PEG in the brain. No adverse test item-related findings were seen and PEG was not detected in the brain. Exposure was confirmed for ~75% of the animals dosed with 500 and 1200 IU/kg N8-GP; the high lower limit of quantification of the bioanalysis assay prevented confirmation of exposure in the lower doses. A small number of animals developed ADAs, and the proportion of animals surviving until scheduled termination was >80%. N8-GP was well tolerated, and the immune-deficient rat proved suitable for testing long-term toxicity of human proteins that are immunogenic in animals.